Influence of the Construction of the Urdinbide Road Tunnel on the Autzagane Aquifer in Biscay (Spain) - José-Manuel Baraibar; Miguel Gil; Iñigo Escobal (Applied Sciences, 2023)
The Urdinbide road tunnel goes through the Autzagane aquifer. This important aquifer is located within the hydrogeological area of the Urdaibai Biosphere Reserve, one of the most important biosphere reserves in the Iberian Peninsula, and it is also used as a source of drinking water for some urban areas in the municipality of Amorebieta-Etxano. The construction of the tunnel could pose a potential risk to the normal functioning of the aquifer, so its design included a special procedure for injecting cement and microcement to waterproof the surrounding area of the drilling, preventing the tunnel from functioning as a drain for the aquifer. The project initially included an intensive hydrogeological characterization of the rock massif, as well as a monitoring phase during the construction works, which allowed a real-time verification of the influence of the tunnel construction on the functioning of the aquifer and the restoration of its normal functioning once the works were completed. The work carried out has shown that the construction of the tunnel has not caused a significant impact on the Autzagane aquifer.